PEDAGOGICAL CONDITIONS OF STUDENTS’ PERSONAL AND PROFESSIONAL GROWTH IN THE CONTEXT OF VOLUNTEER ACTIVITYIES - M. M. MAZNICHENKO; G. S. PAPAZYAN (Высшее образование в России)
In connection with the implementation in recent years of large-scale projects in Russia, in particular the Winter Olympic and Paralympic Games of 2014, student volunteering has become an integral component of higher education. At the IV All-Russian Student Forum in 2011, the President of the Russian Federation Dmitry Medvedev noted that “Today volunteerism is a key theme of the development of our country.” Volunteering remains the key agenda today, including in connection with the preparations for the FIFA-2018 World Cup in Russia. The completed studies (L.E. Sikorskaya, N.V. Cherepanova, S.G. Ekimova, G.G. Borodaeva, I.A. Rudneva, T.N. Arsen’eva, M.V. Pevnaya, V.A. Starodubtsev, P.V. Rodionov, A.F. Kozodaeva, J. Wilson, P.A. Ambarova, R.A. Stebbins) substantiate the high development potential of volunteering. However, the analysis of university practice shows that it is practically not used by students because of the fact that the pedagogical conditions necessary for this are not scientifically grounded and are not being created in universities. The purpose of this article is to justify the conditions for personal and professional growth of students in the context of volunteerism, the development of universal and professional competencies, and civil qualities.